Process Optimization for Enhanced Dimethyl Ether Yield through Methanol Synthesis and Dehydration of Syngas-Derived Methanol - Gayuh Tahta Aditama Nugraha; Fardan Akbar Maulana; Muhammad Erlangga Pratama; Muhammad Hamim Safrudin; Fauzan Aqil Afdika (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
The global energy crisis and continued reliance on fossil fuels highlight the urgent need for sustainable alternatives. Dimethyl ether (DME) has emerged as a promising low carbon fuel owing to its clean combustion properties and versatility as an LPG substitute, diesel replacement, and chemical feedstock. This study focuses on optimizing the design of DME production from syngas derived methanol, with particular emphasis on conversion efficiency and thermal management. Base case simulations revealed that higher methanol dehydration conversion elevated reactor temperatures by nearly 100 °C, thereby disrupting equilibrium and hindering effective separation. To address these challenges, a modified process integrating cooling, heating, and distillation units was developed, achieving an 80% conversion and a DME yield of 97.6%, while simultaneously reducing excessive cooling requirements. These findings demonstrate that improved thermal control and separation strategies can significantly enhance both energy efficiency and environmental performance, reinforcing DME’s potential role in the transition toward cleaner energy systems. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).